Effect of a Concurrent Training Program with and Without Metformin Treatment on Metabolic Markers and Cardiorespiratory Fitness in Individuals with Insulin Resistance: A Retrospective Analysis - Aedo-Munoz, E (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Background: Type 2 diabetes mellitus is a metabolic disorder characterized by insulin resistance (IR), which is prevalent worldwide and has significant adverse health effects. Metformin is commonly prescribed as a pharmacological treatment. Physical exercise is also recognized as an effective regulator of glycemia, independent of metformin. However, the effects of inter-day concurrent training (CT)—which includes both endurance and resistance exercises—combined with metformin treatment on metabolic markers and cardiorespiratory fitness in individuals with IR remain controversial. Objective: This study aimed to analyze the effects of a 12-week inter-day CT program on metabolic markers and cardiorespiratory fitness in overweight/obese individuals with IR, both with and without metformin treatment. Additionally, inter-individual responses to CT were examined. Materials and Methods: Data from the 2022–2023 Obesity Center database were retrospectively analyzed. According to the eligibility criteria, 20 overweight/obese individuals diagnosed with IR participated in a 12-week CT program (three weekly sessions: two endurance and one resistance exercise session). Participants were divided into three groups: the exercise group (E-G: n = 7, 32.86 ± 8.32 years, 85.2 ± 19.67 kg), the exercise–metformin group (E-MG: n = 6, 34.83 ± 12.91 years, 88.13 ± 12.66 kg), and the metformin-only control group (M-G: n = 7, 34.43 ± 13.96 years, 94.23 ± 13.93 kg). The M-G did not perform physical exercise during the 12 weeks but continued pharmacological treatment. Body composition, metabolic markers, and cardiorespiratory fitness were assessed before and after the 12-week CT program. Results: A group-by-time interaction was observed for fasting insulin (F2,17 = 34.059, p < 0.001, η2p = 0.88), the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) (F2,17 = 35.597, p < 0.001, η2p = 0.80), and maximal fat oxidation (MFO) (F2,17 = 4.541, p = 0.026, η2p = 0.348) following the CT program. The maximal oxygen uptake (VO2max) showed significant improvements in the E-G (F = 4.888, p = 0.041, ∆+13.3%). Additionally, the percentage of fat mass (%FM) and body mass (BM) were significantly reduced across all groups (F = 125.244, p < 0.001 and F = 91.130, p < 0.001, respectively). The BM decreased by ∆−9.43% in the E-G (five responders, Rs), ∆+9.21% in the EM-G (5 Rs), and ∆+5.15% in the M-G (3 Rs). The %FM was reduced in the E-G by ∆−22.52% (seven Rs). Fasting insulin and the HOMA-IR significantly improved in both the E-G and EM-G, with fasting insulin showing a ∆−82.1% reduction in the E-G (five Rs) and a ∆−85% reduction in the EM-G (six Rs). Similarly, the HOMA-IR improved by ∆+82.6% in the E-G (three Rs) and by ∆+84.6% in the EM-G (six Rs). Conclusions: The 12-week inter-day concurrent training program, whether combined with metformin or not, was similarly effective in improving metabolic markers in patients with insulin resistance as metformin treatment alone. Both exercise groups demonstrated a significant reduction in insulin sensitivity and an increase in maximal fat oxidation. Meanwhile, exclusive pharmacological treatment with metformin markedly decreased cardiorespiratory fitness, and consequently, fat oxidation. © 2024 by the authors.